The Role of Women in Climate Change Adaptation in Langkai Island, Makassar, Indonesia - Sun Efrianti Rauf (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
This study aims to determine women's role in climate change adaptation on Langkai Island. This study uses a descriptive qualitative approach to describe the role of women on Langkai Island as an adaptation to climate change. The research was conducted on Langkai Island, Makassar, Indonesia, July 5-10, 2024. The informants numbered 12 people, including women, members of non-governmental organizations (NGOs), and local government officials. The results show that women on Langkai Island have an important role in families and coastal communities, managing small businesses and processing their husbands' catches, as part of climate change adaptation. They formed the Merpati Putih business group to address income instability, which processes octopus and fish into value-added products. Empowerment programs that improve financial skills and literacy help them manage family finances, reduce debt, and improve economic stability while contributing to the sustainability of coastal ecosystems.